Research on the Challenges and Countermeasures of Data Governance in Government Public Management in the Era of Artificial Intelligence - Huang, Yanfei (International Journal of Social Sciences and Public Administration, 2026)
In the process of the development and application of artificial intelligence technology in government public management, data has gradually become an important resource for realizing the modernization of government governance system and governance capacity, as well as improving the level of government intelligence. The article focuses on analyzing the data governance dilemma and its causes faced by government public management under the background of artificial intelligence, and discusses aspects such as data itself, technological support, management systems, and social concepts. Finally, corresponding countermeasures and suggestions are provided, such as creating a high-quality data resource environment, improving technical support and security levels, improving institutional norms and collaborative networks, and building a shared and friendly social atmosphere, in order to contribute to enhancing the data management level of Chinese governments at all levels, promoting the process of intelligent public management, and realizing the modernization of national governance capacity and governance system.